2005
DOI: 10.1002/pssa.200590018
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of twins in glass‐embedded silver nanoparticles of various origin

Abstract: The present issue of physica status solidi (a), guest‐edited by Wolfgang Neumann, is dedicated to Professor Johannes Heydenreich, member of the Advisory and Editorial Board since 1986, on the occasion of his 75th birthday. The journal cover shows a transmission electron micrograph of a cyclic twinned silver nanoparticle in 〈110〉 zone axis orientation that contains two pairs of stacking faults in one twin segment. The stacking sequence of atomic layers in between twin boundaries 4 and 5 is depicted in a schemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 1 publication
1
4
0
Order By: Relevance
“…A close inspection of Figure 4d revealed the presence of twin boundaries in Ag NP, especially in the areas near the surface of the particle. This observation is indeed in good agreement with the results of other experiment, 58 where the twin boundaries were observed to be prevalent in the Ag NP within the glass matrixes.…”
Section: ' Resultssupporting
confidence: 93%
“…A close inspection of Figure 4d revealed the presence of twin boundaries in Ag NP, especially in the areas near the surface of the particle. This observation is indeed in good agreement with the results of other experiment, 58 where the twin boundaries were observed to be prevalent in the Ag NP within the glass matrixes.…”
Section: ' Resultssupporting
confidence: 93%
“…Figures 7a-c show examples of images of rapidly grown platelet-like particles of Au, which contain parallel twins that each have a thickness of a few atomic layers, as previously reported for Ag [22]. It has been suggested that alloying may reduce some of the problems that result from abnormally rapid growth if the alloy increases the twin boundary energy at the grooves.…”
Section: Three-dimensional Shapes Of Ltpsmentioning
confidence: 59%
“…Weak-beam dark-field imaging has been used to identify icosahedral structures in Rh particles [19]. MTPs have also been imaged in detail using high-resolution TEM (HRTEM) [20][21][22]. The primary disadvantage of HRTEM is that it may provide poor statistics resulting from small numbers of observations.…”
Section: Introductionmentioning
confidence: 99%
“…These features are rather similar than those found in silver nanoparticles embedded in glass. 40,41 The addition of 1-decanethiol (C 10 H 21 SH) or 1-dodecanethiol (C 12 H 25 SH) to the as-prepared colloidal suspension typically slightly reduces the mean nanocrystal size and the presence of twin faults; on the other hand, it does not modify significantly the uniformity and the cuboctahedron shape of the AuNCs. As illustrative examples, Figure 1S (see the Supporting Information) shows the HRTEM analysis of a decanethiol-capped AuNC with similar characteristics than those observed in Figure 3a, and Figure 2Sa,b (see the Supporting Information) depicts the HRTEM and FFT analyses of a cuboctahedral dodecanethiol-capped AuNC viewed along the [001] zone axis, respectively.…”
Section: Resultsmentioning
confidence: 99%